2018
DOI: 10.1021/acs.jchemed.8b00266
|View full text |Cite
|
Sign up to set email alerts
|

Demonstrating the Photochemical Transformation of Silver Nanoparticles

Abstract: A laboratory experiment is described in which students synthesize silver nanospheres and transform them into other anisotropic morphologies (decahedral and disks) through a photochemical process. The photochemical transformation was followed by visible spectroscopy, and the resulting morphologies were analyzed using scanning electron microscopy. This experiment, which may be included in a nanotechnology or materials chemistry laboratory course, introduces students to nanotechnology and shows how anisotropic na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Sigmoidal Boltzmann fitting in Origin (see the SI) should only be followed for the kinetics and t 50 calculations. Exposure to light during the synthesis can affect both reactants (photoreduction/photo-oxidation may alter the t 50 value) as well as the yield of product NCs (photodecomposition which is observed in many silver NPs). Using other fitting equations might affect the t 50 calculation.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sigmoidal Boltzmann fitting in Origin (see the SI) should only be followed for the kinetics and t 50 calculations. Exposure to light during the synthesis can affect both reactants (photoreduction/photo-oxidation may alter the t 50 value) as well as the yield of product NCs (photodecomposition which is observed in many silver NPs). Using other fitting equations might affect the t 50 calculation.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Nanoclusters (NCs) are a subset of these materials which bridge the gap between NPs and atoms. , Because of their ultrasmall size (1–2 nm), they show unusual optical and photophysical properties. These NCs may be atomically precise with a well-defined molecular formula, e.g., Au 25 (SR) 18 , Ag 29 (SR) 12 (SR represents the thiolate which acts as the ligand), etc. More than 100 such NCs are currently known, and extensive research has already been done to explore their promising properties and applications. , Over the past few years, fluorescent NCs became more popular because of their intrinsic fluorescence properties which can be used in many biological and sensor-based applications. , While the synthesis and characterization of metal NPs have appeared in many chemical education publications, there are few didactic reports to transfer the knowledge of NC synthesis, characterization, and application. One example in this direction described a microwave-based synthesis of Au NCs using proteins as a stabilizing agent .…”
Section: Introductionmentioning
confidence: 99%
“…As the field of nanoscience expands, there is an urgency for nanoscience education and emerging analytical techniques for high school students and undergraduates. Nanochemistry undergraduate laboratory experiments dedicated to nanoparticle–protein interactions are currently limited in scope. Most of these have focused on spectroscopic characterization such as UV–vis spectroscopy to investigate the plasmonic properties of silver and gold nanoparticles. , There are also relatively few NMR spectroscopy-based undergraduate laboratories that focus on proteins. Of these, most explore protein–small molecule interactions through enzyme kinetics or small molecule binding. ,, The most advanced of these undergraduate NMR experiments provides students with a 13 C- and 15 N-labeled sample and explores contemporary NMR assignment strategies in an 11 week course . None of these experiments, however, examines protein binding in the context of nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…As shown by Zielińska et al, silver colloids exhibiting diverse plasmonic features are possible using chemical reduction routes involving various combinations of silver precursor (e.g., nitrate, acetate, or citrate salts), reducing agent (e.g., ascorbic acid, hydrazine, sodium borohydride), and stabilizing agent (e.g., polyvinyl pyrrolidone, polyvinyl alcohol) . Although many publications in this Journal address NC systems ,, and silver specifically, ,, these studies promote rapid synthesis and application, with NC aggregation being shown as a preventable outcome rather than a pedagogical focus. We propose that an appropriate visual demonstration involving growth and aggregation of colloidal AgNCs should provide a color transition that lasts for several minutes, allowing for extended observation and discussion of the relevant chemistry.…”
Section: Introductionmentioning
confidence: 99%